Structural, magnetic and electrical properties of barium titanate and magnesium ferrite composites - Mohamad Fahmi Amin Zolkepli,; Zalita Zainuddin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Structural, magnetic and electrical characteristics of multiferroics (1-x)BaTiO3-xMgFe2O4 composites with weight fractions of x = 0.3, 0.5 and 0.7 are reported. MgFe2O4 powders were prepared using sol-gel auto combustion technique. It was combined with commercial BaTiO3 to form composites by using wet milling solid state reaction technique. Formation of tetragonal perovskite for the ferroelectric BaTiO3 and cubic spinel for the ferrimagnetic MgFe2O4 phases, were identified from the XRD pattern. The average grain size for each composite was about 0.5 μm. The M-H loop showed soft ferrimagnetic properties due to the presence of MgFe2O4 in the composites. The increment of the MgFe2O4 weight fraction increased the saturation magnetization and slightly changed the coercive field. The complex impedance plot can be represented by a parallel R and C circuit. Composite sample with x = 0.5 has the highest resistance with lowest capacitance and dielectric constant value at room temperature. The dielectric constant showed a very strong dispersion at low frequencies, due to the Maxwell-Wagner mechanism and a slight dispersion at higher frequencies. Based on the results obtained, all of the composite samples exhibited high dielectric constant and tangent loss at the low frequency range.